Deciphering the role of molecular mimicry in the etiopathogenesis of Autoimmune Hemolytic Anemia using an immunoinformatics approach. - Pratyusha Patidar; Arihant Jain; Tulika Prakash (ImmunoInformatics)
Autoimmune hemolytic anemia (AIHA) is a chronic autoimmune disease characterized by the self-destruction of red blood cells (RBCs). For investigating the role molecular mimicry in the onset of AIHA manifestations, we identified the microbial epitopes as precipitating factors in the disease etiopathology using an integrated immunoinformatics pipeline which includes sequence homology search between microbial and RBC proteins, followed by B-cell and T-cell epitope prediction. These epitopes were further subjected to a homology search with the human gut microbial proteins. Eight out of the ten analysed infectious agents, including Hepatitis C Virus (HCV), Cytomegalovirus (CMV), Epstein-Barr Virus (EBV), Herpes Simplex Virus (HSV), Human Papillomavirus (HPV), Human Immunodeficiency Virus (HIV), Mycoplasma pneumoniae (MP), and Treponema pallidum (TP), possessed B-cell and T-cell epitopes. Interestingly, EBV, HSV, MP, and TP displayed conformational B-cell epitopes, which overlapped with their linear B-cell epitopes. HLA DRB1_0305 was found to exhibit binding with several bacterial epitopes indicating its predisposing potential to AIHA. Further, we report cross-reactive microbial epitopes against RBC proteins that have been experimentally proven to be associated with AIHA indicating a high possibility of those epitopes causing AIHA. Additionally, many B-cell and T-cell epitopes exhibited exact homologies with various human gut microbial proteins. The functional annotation highlighted the involvement of specialized RBC functions, such as cytoskeleton organization, ammonium homeostasis, signalling transduction, in the underlying disease mechanism. These findings suggest that infection-causing pathogens and gut microbes might have a plausible association with AIHA in the context of molecular mimicry.